Transitioning to Zero Hunger (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
In 2015, the United Nations decided to establish the goal of achieving “zero hunger” in the world by 2030 through “outcome targets” such as eliminating hunger and improving access to food, ending all forms of malnutrition, promoting sustainable and resilient agriculture, and maintaining genetic diversity in food production. As a result of this decision, strategies are under way in different countries around the world in the form of political, academic, development, and non-governmental organization projects and programs. Five years later, these strategies have certainly generated results that need to be documented and analyzed so as to answer the following questions: what are the progress and success stories in terms of policies, innovations, technologies, and approaches to reach the zero hunger goal? What are the constraints and mitigation strategies? Are we really in a phase of transition towards the zero hunger goal? What new directions do we need to consider to achieve this goal, particularly in the context of the current COVID-19 pandemic, which affects all sectors of development around the world? This book volume will be published within MDPI’s new open access book series entitled “Transitioning to Sustainability”. It welcomes contributions of empirical research, position pieces, and presentations of important research programs or stakeholder initiatives that cover any of the four “outcome targets” of the zero hunger goal. The contributions may come from academics, students, and policy makers of any region in the world and may be related to specific disciplines or be inter and/or transdisciplinary. They may cover areas including but not limited to sustainable improvement of food production, implementing sustainable food and farming systems, improving access to food, limiting malnutrition, limiting food loss and food waste and, finally, global analyses of the challenges of reaching zero hunger in relation to other sustainable development goals as well as success stories on projects, programmes or government initiatives. Transitioning to Zero Hunger is part of MDPI's new Open Access book series Transitioning to Sustainability. With this series, MDPI pursues environmentally and socially relevant research which contributes to efforts toward a sustainable world. Transitioning to Sustainability aims to add to the conversation about regional and global sustainable development according to the 17 SDGs. Set to be published in 2020/2021, the book series is intended to reach beyond disciplinary, even academic boundaries.